Literature Review: Network Pharmacology as a New Approach and Trend in Medicine - ihya, Zahratul; Irfandi, Rizal; Rijal, Syamsu; Yani, Ahmad; Arafah, Muhammad; Badli Rompegading, Andi (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2024)
Network pharmacology is a new approach to medicine that aims to understand drug interactions with body tissues more specifically. This concept involves a deep understanding of the mechanisms of drug action, drug metabolism, and the influence of drugs on tissue function. In recent years, network pharmacology has become a significant trend in drug development. This approach allows researchers to design drugs that are more effective and have fewer side effects. By understanding in detail how drugs interact with specific tissues, specific and targeted drug development can be undertaken. Network pharmacology also opens the door to the development of more particular and existent therapies. By taking into account individual differences in response to drugs, this approach allows for more effective and safer treatment. This article presents a literature review of network pharmacology as a new approach and trend in medicine. This literature review also explores the latest research and current trends in the world of medicine using a network pharmacology approach.This article shows that tissue pharmacology has great potential in more effective and safer treatments. With a better understanding of drug - tissue interactions, we can develop more targeted therapies and reduce the risk of undesirable side effects.